Lebanon : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
The Selected Issues paper of Lebanon provides an update of the vulnerability assessment based on the balance sheet approach. It explores the interest rate determination, the strength of the link to international interest rates, and exposure to international interest rate shocks, summarizes the methodology used to derive confidence intervals around the path of the debt ratio in the staff's adjustment scenario, and provides an assessment of Lebanon's competitiveness from a macroeconomic and microeconomic perspective, with a view to identify possible sources of competitiveness gains over the medium term.